Quantum-Inspired Algorithms for Market Clearing in Smart Grids: A Comprehensive Review - Jha, Rahul Kumar (Recent Research Reviews Journal, 2023)
The integration of smart grids into modern power systems marks a fundamental shift, leveraging cutting-edge technology to enhance system efficiency and optimize energy distribution. At the heart of this transformation lies the concept of market clearing, a pivotal procedure facilitating effective energy trading and resource allocation within smart grids. This research explores the significance of market clearing in smart grids and introduces the transformative realm of quantum-inspired algorithms, poised to revolutionize energy market control systems.
Keywords: Quantum-Inspired Algorithms; Market Clearing; Smart Grids; Optimization Techniques; Energy Trading